2017
DOI: 10.1016/j.eats.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Internal Suture Augmentation Technique to Protect the Anterior Cruciate Ligament Reconstruction Graft

Abstract: The anterior cruciate ligament suture augmentation technique is a method to augment anterior cruciate ligament reconstruction (ACLR) with autologous hamstring tendons using a braided ultrahigh–molecular weight polyester or polyethylene suture or suture tape and fixed on both the femoral and tibial sides independent of the graft to act as a backup or secondary stabilizer until complete integration and ligamentization of the graft take place. The technique is proposed to allow early rehabilitation and return to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…[3][4][5][6][7] In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. [8][9][10]12,13 However, in a cadaveric study, Lai et al 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts. There was also a surgical technique using multiple suture strands to augment ACL which was reported by Kuptniratsaikul et al 15 The suture acts as a structural tie before fully ligamentization of the ACL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7] In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. [8][9][10]12,13 However, in a cadaveric study, Lai et al 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts. There was also a surgical technique using multiple suture strands to augment ACL which was reported by Kuptniratsaikul et al 15 The suture acts as a structural tie before fully ligamentization of the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. 8 , 9 , 10 , 12 , 13 However, in a cadaveric study, Lai et al. 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Suture tape augmentation/reinforcement has been performed in an attempt to improve results after primary ACL reconstruction. 10 , 11 , 12 , 13 Interest in augmenting grafts during ACL reconstruction stems from the biomechanical and clinical success of suture augmentation in non-knee-related procedures such as Brostrom repairs 17 and ulnar collateral ligament repairs in the elbow. 18 Promising outcomes have also been seen in conjunction with medial knee injuries 19 , 20 and ACL repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in an attempt to improve clinical outcomes, suture tape augmentation/reinforcement ( Internal Brace; Arthrex, Naples, FL) has been described in both hamstring autografts and allografts. 10 , 11 , 12 , 13 The Internal Brace is composed of a FiberTape (Arthrex) suture, an ultrahigh-molecular-weight polyethylene/polyester tape that is collagen coated to increase tissue integration. Purported advantages include protection of the graft during the proliferation, maturation, and ligamentization phases of healing.…”
mentioning
confidence: 99%